HUBUNGAN ANTARA KEAKTIFAN IBU DALAM KEGIATAN POSYANDU DENGAN STATUS GIZI BALITA (Jurnal Medika : Karya Ilmiah Kesehatan, 2019)
The purpose of this study was to determine the correlation between the mother’s liveliness in Posyandu activities with the toddler nutritional status. This study was analytical survey with cross sectional design. The samples of this study were 38 samples with accidental sampling technique. The result of the study was kolmogorov alternative test obtained liveliness with nutrient status that significant p value 0,000 (
Keywords: Toddler, Nutritional Status , Mother’s Liveliness Posyandu